STUDI EKSPERIMENTAL: MENGURANGI BIAS PENGUKURAN UMUM BALANCE SCORECARD DALAM PENILAIAN KINERJA PADA MAHASISWA SI PROGRAM MANAJEMEN PARIWISATA - Janet, Georgina (Business Accounting Review, 2015)
The study Lipe & Salterio (2000) found a common measurement dominance on the results of the performance evaluation using the BSC, and this has resulted in a common measure bias. Various approaches are taken to address the common measure bias, but was not optimally reduced the common measure bias.This study combined two approaches which were disaggregate / mechanically aggregate and knowledge to reduce the common measure bias. The study also examined whether the performance evaluation using the BSC affected the allocation of compensation. This study used an experimental research method. The first hypothesis was tested by using repeated measures ANOVA, the second hypothesis was tested by using independent sample t-test and the second hypothesis was tested by using multiple linear regression. The Disaggregate /mechanically aggregate and knowledge approaches were managed to reduce the common measure bias ofÂ BSC andÂ the results of BSC performance evaluation influenced the allocation of compensation.